Suplementação de um probiótico para frangos de corte submetidos ao estresse térmico - Reis, Matheus de Paula (2016)
Three independent trials were conducted with broiler chickens raised from one to 42 days old, in order to evaluate the effect of a probiotic supplementation (Bacillus subtilis - DSM 17299) for broilers chickens. The first trial was conducted in metabolic cages and consisting of two treatments, with and without probiotic supplementation. We evaluated the performance of the birds weekly, the apparent ileal digestibility of crude protein (ADCP) and dry matter (ADDM) and energy content of diets (AME) for two periods, 18-21 days and 38 to 41days. It also evaluated the pH of the gastro intestinal tract (GIT) contents. Trial II was conducted in colonial houses consisting of two treatments until 21 days of age (with and without probiotic) and 4 treatments in a factorial design 2 x 2 (with and without probiotic x with and without heat stress (HS)) from day 22. The response variables evaluated were the pH of the GIT contents, relative organ weight (RW) and relative length (RL) of the segments from small intestine. The third trial followed the same distribution as the trial II, however, the measurement evaluated were performance and the morphology of the GIT. A positive influence of the probiotic supplementation on performance measurements, in which there were improvements in feed conversion ratio (FCR), a result of an improvement on feed efficiency of birds supplemented with the probiotic. It was observed a statistical difference in the pH of the intestinal contents, where the pH measurements were increased by probiotic supplementation, mainly, on ileum at days 14th and 42sd. Supplemented birds showed a reduction in the weight and length of the duodenum, with a consequent increase of the same measurement in the jejunum and ileum. The study of intestinal morphology demonstrated that improvements in nutrient uptake might have been a result of an increase in absorptive surface of the GIT. Except for the crypt depth at 42 days of age, there was no interaction between the factors studied to any measurement or assessed age, demonstrating that the effect of probiotic has not changed with the stress of the birds by an increase of the temperature. The results of this study demonstrated that probiotic consisting of B. subtilis DSM 17299 has a beneficial effect, even in birds subjected to high temperature conditions, contributing to the increase in feed efficiency of the poultry, which can reduce production costs of broilers, bringing greater benefits for the poultry industry.